El mecanismo disruptivo de regularización en la ley española que desafía la reforma del Sistema Europeo Común de Asilo - García-Juan, Laura (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
The debate regarding the extent of EU Member States competences in immigrant integration policies was paused with the Treaty of Lisbon. European institutions took an active role in integration but did not mandate a communal approach. Consequently, each Member State instigated its own policies, which led to a wide diversity of regulations. The policy adopted by Spain stands out because of its particular approach to integration policies, which in this case are applicable to regular and irregular immigrants. A remarkable feature of the migration law in Spain is that it contains a regularisation mechanism for irregular immigrants that does not require them to have a visa in order to obtain the status of temporary residency. This mechanism is known as arraigo social (social ties). In these cases, access to regularity depends on the level of social integration that the immigrant can prove to have achieved. This article analyses the statistics on the use of this mechanism in Spain and discusses whether it could offer a path to asylum seekers looking for an official response after several years of waiting in the EU.